2016
DOI: 10.1103/physrevb.94.245108
|View full text |Cite
|
Sign up to set email alerts
|

Exact special twist method for quantum Monte Carlo simulations

Abstract: We present a systematic investigation of the special twist method introduced by Rajagopal et al. [Phys. Rev. B 51, 10591 (1995)] for reducing finite-size effects in correlated calculations of periodic extended systems with Coulomb interactions and Fermi statistics. We propose a procedure for finding special twist values which, at variance with previous applications of this method, reproduce the energy of the mean-field infinite-size limit solution within an adjustable (arbitrarily small) numerical error. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 74 publications
0
30
0
Order By: Relevance
“…In most calculations we consider 24 carbon atoms in an orthorombic supercell with rectangular basis, whereas for the size scaling of Fig.3b (main text) we use also 12, 36, 48, and 96 carbon supercells. In order to minimize finite-size effects, we adopt the twist-averaged-boundary conditions [44][45][46] in the x and y directions with averaging over a 6 × 8 Monkhorst-Pack grid [39], whereas in the z direction, we adopt simple periodic-boundary conditions with a very large distance (300 Bohrs) between the graphene images. In order to minimize the number of variational parameters and achieve a faster and smoother convergence in…”
Section: Quantum Monte Carlo Calculationmentioning
confidence: 99%
“…In most calculations we consider 24 carbon atoms in an orthorombic supercell with rectangular basis, whereas for the size scaling of Fig.3b (main text) we use also 12, 36, 48, and 96 carbon supercells. In order to minimize finite-size effects, we adopt the twist-averaged-boundary conditions [44][45][46] in the x and y directions with averaging over a 6 × 8 Monkhorst-Pack grid [39], whereas in the z direction, we adopt simple periodic-boundary conditions with a very large distance (300 Bohrs) between the graphene images. In order to minimize the number of variational parameters and achieve a faster and smoother convergence in…”
Section: Quantum Monte Carlo Calculationmentioning
confidence: 99%
“…In the case of weakly correlated systems, size effects are most pronounced and calculations of observables with a single boundary condition such as PBC or anti-periodicboundary condition (APBC) may have serious difficulties in determining the correct thermodynamic limit. In order to mimic the Brillouin zone of the thermodynamic limit, TABCs have been proposed and indeed it has been shown that TABCs eliminate one-body error very successfully [25,26,28].…”
Section: Twist-averaged Boundary Conditionsmentioning
confidence: 99%
“…In order to control the finite size effects discussed above, twist-averaged boundary conditions (TABCs) have been introduced for Monte Carlo simulations on lattice model [22][23][24][25][26][27] and in continuum systems [28,29]. Within TABCs, physical quantities are estimated by averaging them over several twisted-boundary conditions [30], rather than limiting the calculation to a single twist, such as PBC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At variance of Refs. [16,38] we take care of finite size-effects using a recently developed [39] k− point sampling of the Brillouin zone [40,41] (BZ). In most simulations we use a cubic supercell containing 64 atoms and a 4×4×4 Monkhorst and Pack k-point mesh, which looks clearly consistent with larger systems calculations (see Fig.…”
mentioning
confidence: 99%